2017
DOI: 10.1016/j.pscychresns.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural changes in late-life generalized anxiety disorder

Abstract: Late-life Generalized Anxiety Disorder (GAD) is relatively understudied and the underlying structural and functional neuroanatomy has received little attention. In this study, we compare the brain structural characteristics in white and gray matter in 31 non-anxious older adults and 28 late-life GAD participants. Gray matter indices (cortical thickness and volume) were measured using FreeSurfer parcellation and segmentation, and mean diffusivity was obtained through Diffusion Tensor Imaging (DTI). We assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…However, it should be noted that a few studies ( n = 3) showed increased FC in the dlPFC (Andreescu et al., 2015 (insula seed); Toazza et al., 2016 (basolateral amygdala seed); Wang et al., 2016a (whole-brain ALFF)). Finally, results indicated that subjects with GAD had reduced dlPFC volume ( n = 5; Andreescu et al., 2017; Moon and Jeong, 2015a, 2016, 2017a, 2017b).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, it should be noted that a few studies ( n = 3) showed increased FC in the dlPFC (Andreescu et al., 2015 (insula seed); Toazza et al., 2016 (basolateral amygdala seed); Wang et al., 2016a (whole-brain ALFF)). Finally, results indicated that subjects with GAD had reduced dlPFC volume ( n = 5; Andreescu et al., 2017; Moon and Jeong, 2015a, 2016, 2017a, 2017b).…”
Section: Resultsmentioning
confidence: 94%
“…1 for flow diagram). Of the included records, 35 included structural analyses (Abdallah et al., 2013; Andreescu et al., 2017; Brambilla et al., 2012; Cha et al., 2016a; Cha et al., 2014b; Cha et al., 2016b; Chen and Etkin, 2013; De Bellis et al., 2000, 2002; Etkin et al., 2009; Hettema et al., 2012; Hilbert et al., 2015; Karim et al., 2016; Liao et al., 2013, 2014a, 2014b; Makovac et al., 2016a; Mohlman et al., 2009; Molent et al., 2017; Moon and Jeong, 2015a, 2016, 2017a, 2017b; Moon et al., 2015a, 2014, 2015b; Mueller et al., 2013; Schienle et al., 2011; Strawn et al., 2014, 2013; Terlevic et al., 2013; Tromp et al., 2012; Wang et al., 2016b; Zhang et al., 2011; Zhang et al., 2013), 32 included FC analyses (Andreescu et al., 2015; Andreescu et al., 2014; Buff et al., 2016; Cha et al., 2014a; Cha et al., 2016b; Chen and Etkin, 2013; Cui et al., 2016; Etkin et al., 2010; Etkin et al., 2009; Etkin and Schatzberg, 2011; Fonzo et al., 2014; Greenberg et al., 2013; Hölzel et al., 2013; Laufer et al., 2016; Li et al., 2018; Li et al., 2016; Liu et al., 2015; Makovac et al., 2016b; Makovac et al., 2018; McClure et al., 2007; Mohlman et al., 2017; Monk et al., 2008; Oathes et al., 2015; Pace-Schott et al., 2017; Qiao et al., 2017; Rabany et al., 2017; Roy et al., 2013; Strawn et al., 2012; Toazza et al., 2016; Tromp et al., 2012; Wang et al., 2016a;…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some structural and functional deficits in this area have been found in fMRI studies in neuropsychiatric disorders, such as generalized anxiety disorder (Andreescu et al 2017) and PTSD (Shvil et al 2014), which both affect severely the extinction of fear memories. In the case of PTSD, interestingly, the activation of ACC, together with the vmPFC and hippocampus, is sexually dimorphic: men with PTSD exhibited increased activation in the left rostral dACC during extinction recall compared to women with PTSD (Shvil et al 2014;Yoon et al 2017).…”
Section: Anterior Cingulate Cortexmentioning
confidence: 99%
“…Cortical thickness measurements were obtained from Freesurfer segmentations. Six regions were selected based on a previous study [2]: left dorsal and rostral ACC, left and right medial orbitofrontal, right pars triangularis and right pars opercularis. We normalized the cortical thickness measurements from each region using the average cortical thickness of the brain.…”
Section: Cortical Thickness Computationmentioning
confidence: 99%
“…Previously in a whole brain analysis we explored the differences between gray matter indices (cortical thickness and volume) in late-life GAD and non-anxious elderly participants. GAD participants had lower cortical thickness in the orbitofrontal cortex (OFC) and dorsal anterior cingulate cortex, and lower cortical volume in inferior frontal gyrus (ACC) [2]. Higher worry severity was associated with lower gray matter thickness in BA24 region (left dorsal and rostral ACC).…”
Section: Introductionmentioning
confidence: 99%